PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE DALAM MENINGKATKAN PEMAHAMAN PESERTA DIDIK MENGENALI HURUF HIJAIYAH DI KELAS 2 SDN 1 SILEA - Ahmad Nabilal; M. Zakariah (Universitas Sains Islam Al Mawaddah Warrahmah Kolaka, 2025)
The learning implementation that occurs at SDN 1 Silea is considered to lack variety in learning, making learning monotonous. The basic difficulty in recognizing hijaiyah letters is the difficulty in naming, showing and differentiating hijaiyah letters which have similar shapes but differ in pronunciation. This is in accordance with initial observations made previously on grade 2 students at SDN 1 Silea. Only a small percentage of students understand the level of mastery, of 19 students only 26% succeed. This shows that the learning process was not successful. The problem that can be raised in this research is how the learning process is in recognizing hijaiyah letters in class 2 of SDN 1 Silea and how to use the picture and picture learning model to increase students' understanding of recognizing hijaiyah letters in class 2 of SDN 1 Silea. Meanwhile, the aim of the research is to determine the learning process in recognizing hijaiyah letters in class 2 of SD N 1 Silea and to determine the use of the picture and picture learning model in increasing students' understanding of recognizing hijaiyah letters in class 2 of SDN 1 Silea.The research methods used include a qualitative approach with the type of classroom action research (PTK); The research subjects were 19 class 2 students at SDN 1 Silea; The research procedures carried out included four stages, namely action planning, action implementation, observation and reflection; Research instruments include observation sheets, interview guidelines, documentation guidelines and tests. This research is said to be successful if the total of 19 students reaches 70% or overall has reached KKM 70 in the subject of Islamic Religious Education in hijaiyah letter material in the use of the picture and picture learning model. The results of the research showed that the process of learning hijaiyah letters using the repeated lecture and question and answer method used by the teacher was not successful where in initial observations only 5 students completed it with a percentage of 26%. By using the picture and picture learning model on hijaiyah letter material, recognizing hijaiyah letters has increased. Where in cycle I the percentage of students' achievement of learning completeness was 63%, while in cycle II the achievement of learning completeness reached a percentage of 100%.